A strategy to detect the effect of electrode defects on the electrical reliability in multilayer ceramic capacitors. (July 2022) - Zhang, Weichen; Zhu, Chaoqiong; Hui, Kezhen; Zhao, Peiyao; Guo, Limin; Cai, Ziming; Li, Longtu; Wang, Xiaohui
Abstract: Multilayer ceramic capacitors (MLCCs) are indispensable devices to electronic industry due to their high capacitance and good temperature stability, which shares the largest market of passive electronic devices. However, electrode defects could adversely influence the reliability, especially for thin-layer MLCCs. It is important to understand the internal relationship between electrode quality and reliability. In this work, finite element method simulation and Kelvin probe force microscopy measurement are introduced to investigate the surface electric field distribution on the cross section of MLCCs. Successively-enhanced local electric field concentration could be detected in the vicinity of electrode roughness, electrode discontinuity, and pores based on both simulation and experimental methods. In addition, probability density of electric field curves and critical intensification factor are calculated to quantitatively characterize the electric field distribution. Electrical measurement results have revealed that MLCCs with superior electrode quality exhibit high reliability, which is further verified by studying the standard MLCCs with nearly perfect electrodes. This work innovatively utilized the Kelvin probe force microscopy test and statistical quantitative characterization of electric field distribution, which may serve as the common approaches in MLCC industries to help understand the mechanism of electrical failure. Graphical abstract: Image 1 Highlights: Quantitative characterization of inner electrode continuity and roughness in multilayer ceramic capacitors. Kelvin probe force microscopy test verified the results of simulation analysis. Statistical analysis of electric field and introduction of critical intensity factor to measure the breakdown strength. Electrode continuity and roughness have an important impact on the reliability of multilayer ceramic capacitors.